An artificial intelligence-integrated analysis of the effect of drought stress on root traits of “modern” and “ancient” wheat varieties - Licaj, Ilva; Felice, Domenico; Germinario, Chiara; Zanotti, Clarissa; Fiorillo, Anna; Marra, Mauro; Rocco, Mariapina (Frontiers in Plant Science, 2023)
Durum wheat is widely grown in the Mediterranean basin, where in the coming years the harmful effects of drought on crop production, due to global climate change, will be particularly severe.Durum wheat cultivation relies on few "modern" genetically uniform varieties more productive but less tolerant to environmental stress than "traditional" varieties, which are a source of genetic biodiversity to select drought tolerance agronomic traits. The plasticity of the root architecture is crucial for plants to acclimate to unfavorable environments, including restricted irrigation regimes. In this study, we have examined the effect of PEG-6000-simulated drought stress on the roots` morphological and anatomical characteristics of two durum wheat cultivars: the "traditional" Saragolla and the "modern" Svevo, using the "SmartRoot" software, and Scanning Electron Microscopy (SEM). Structural changes were related by HPLC analysis to changes in the concentration of phytohormones involved in the expression of root tolerance to drought. For the analysis of root structural data, Artificial Intelligence (AI) algorithms have been used: their application allowed to predict from root structural traits modified by the osmotic stress the type of cultivar observed and to infer the relationship stress-cultivar type, thus demonstrating that root structural traits are clear and incontrovertible indicators of the higher tolerance to osmotic stress of the Saragolla cultivar.